PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN MIT APP INVENTOR POKOK BAHASAN PYTHAGORAS - Arif Sunaryo; Martin Bernard (IKIP Siliwangi, 2022)
The Research and Development (R & D) method was used in this study to develop interactive mathematics learning media using the Android-based MIT App Invemtor application on the Pythagorean subject which consisted of: (1) needs analysis, (2) initial media development, (3) media validation and media revision, (4) media testing and media revision, (5) final product. Data collection is used through a questionnaire/questionnaire. Validation was carried out by a team of material experts, a team of media experts, and students to determine the feasibility of the media. The results of the assessment given to material experts and media experts use the Guttman scale. While the results of the media assessment to students using a Likert scale with a value range of 1-5. Respondents were students from class IX at SMP Putra Juang, Cianjur, totaling 8 students. The data analysis technique in this research is using descriptive qualitative. The average value of 90.27% was obtained from two media experts in the appropriate category. The average value of 87.5% was obtained from two material experts in the appropriate category. The average value of 93.02% was obtained from the results of field trials with a very feasible category.